Management interventions in pacing a planned financial accounting outsourcing transition - Flinkman, Arja; Gullkvist, Benita; Teittinen, Henri (My University, 2024)
Purpose This paper aims to explore how the time and temporal aspects are managed in a financial accounting outsourcing (FAO) transition process in an international interorganizational context. As a research outcome, the authors identify management interventions of both the service provider (SP) and the outsourcing company (OC) at both the corporate and operational levels. Design/methodology/approach The framework by Huy (2001a, 2001b) was used to analyze the qualitative data, which draw on observations, participation in 32 official meetings during the outsourcing process, informal discussions with key actors from the SP and the OC, and archival data of a single case company. Findings The authors illustrate how the time and temporal aspects of planned accelerated change are managed through management interventions during the FAO transition process. All four ideal intervention types (commanding, engineering, teaching and socializing) were used sequentially but also jointly to complement one another. The pacing was mostly rapid, owing to strong commanding interventions initiating almost every stage. When analyzing the FAO transition process, the authors identified four stages: contact, contract, convergence and control. Moreover, the authors focused on the role of the operational-level managers and accounting specialists of both organizations. The findings indicate that management interventions vary with the management level. Originality/value This study contributes to the interorganizational control literature by considering the time and temporal aspects in planned organizational change and the role of operational-level managers in managing large-scale changes.
Keywords: Case study; Financial accounting outsourcing; Interorganizational control; Management interventions; Temporal aspect; Time; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|